A review of ultrawide bandgap materials: properties, synthesis and devices. Issue 1 (5th May 2022) - Xu, Mingfei; Wang, Dawei; Fu, Kai; Mudiyanselage, Dinusha Herath; Fu, Houqiang; Zhao, Yuji
Abstract: Ultrawide bandgap (UWBG) materials such as diamond, Ga2 O3, hexagonal boron nitride (h-BN) and AlN, are a new class of semiconductors that possess a wide range of attractive properties, including very large bandgap, high critical electric field, high carrier mobility and chemical inertness. Due to these outstanding characteristics, UWBG materials are promising candidates to enable high-performance devices for power electronics, ultraviolet photonics, quantum sensing and quantum computing applications. Despite their great potential, the research of UWBG semiconductors is still at a nascent stage and represents a challenging interdisciplinary research area of physics, materials science and devices engineering. In this review, the material properties, synthesis methods and device applications of UWBG semiconductors diamond, Ga2 O3, h-BN and AlN will be presented and their recent progress, challenges and research opportunities will be discussed.